Full waveform inversion of seismic reflection data from the Forsmark planned repository for spent nuclear fuel, eastern central Sweden - Zhang, F.; Juhlin, Christopher (2013)
The Swedish Nuclear Fuel and Waste Management Company (SKB) has been carrying out extensive studies at the planned repository for spent nuclear fuel at the Forsmark site in the eastern part of central Sweden since 2002. Identification of subhorizontal to gently dipping seismic reflections is especially important since these may represent transport routes for radionuclides. Studies have shown that such reflections can be generated by water filled fracture zones that have a lower velocity than the surrounding bedrock. Lithological changes, that is, mafic sills, may also be responsible for reflections in some cases. At the Forsmark site, it is difficult to distinguish fracture zones from mafic sills in the standard reflection seismic processed sections. However, since mafic sills usually have a positive velocity contrast with the background velocity field compared to fractures zones that have a negative one, the two possibilities could be differentiated if we could reconstruct the underground velocity field. Seismic full waveform inversion has the potential to perform this reconstruction, allowing us to discriminate between fractures zones and mafic sills. In this study, we apply a 2-D waveform inversion code on crooked line data sets acquired at the Forsmark site. This implies we are dealing with a 3-D geometry. We handle this problem by applying 3-D to 2-D coordinate projections. First, we perform a synthetic benchmark test with a similar geometry to that of the projected real data. We test both amplitude and phase inversion and phase only inversion on the synthetic data. The results show that the phase only inversion has fewer artefacts and is more stable. After successful application on the synthetic data, we apply the phase only waveform inversion on the real data. The resulting velocity fields show more details compared with the starting model based on first arrival traveltime tomography. Time domain synthetic data sets generated from the final velocity fields show a good match between the early arriving phase of the real data and the synthetic data sets. Checkerboard tests are also applied on the final models for resolution checks and indicate good resolution down to 200m in the central parts of the profiles. Based on a comparison between the Kirchhoff pre-stack depth migrated sections and the final waveform inversion results we conclude that the reflections investigated most likely are generated at low-velocity fracture zones. © The Authors 2013. Published by Oxford University Press on behalf of The Royal Astronomical Society.